Brexit and the International Law Prohibitions on the Loss of eu Citizenship - Worster, William Thomas (International Organizations Law Review, 2018)
This submission challenges the presumption that uk nationals will lose eu citizenship following Brexit. Until now, the dominant narrative has been drawn from the law on treaties or international organizations, and this article adds the human rights perspective to Brexit. Firstly, eu citizenship can be assimilated to nationality. While eu citizenship is unique, the status protected under international law is a legal bond a person has with a political entity. This protection certainly covers nationality, and this paper argues it can be understood to also protect eu citizenship. Secondly, international law prohibits arbitrary withdrawal of this legal bond with a person. The uk does not have jurisdiction over eu citizenship, so it is doubtful the uk can terminate eu citizenship unilaterally. Even if the eu were to withdraw eu citizenship on its initiative, it would still constitute retroactive law, discrimination, and infringement of sovereignty. It is also disproportionate, because the loss of eu citizenship is not necessary for Brexit. When Greenland withdrew from the eu , its residents retained eu citizenship. For these reasons, the revocation of eu citizenship would be arbitrary. A distinction must be made between the membership of a state in the eu which can be terminated, and the direct legal bond formed between a person and the Union, which is far harder to revoke. On this basis, any uk national who has acquired eu citizenship prior to Brexit, should not be divested of it following Brexit.